PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, DAN KECERDASAN SPIRITUAL TERHADAP KINERJA MELALUI KEPUASAN KERJA TENAGA KEPENDIDIKAN DI KANTOR PUSAT UNIVERSITAS JEMBER - Sibasopait, Adeharda Boru (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
The purpose of this study is to significantly prove the direct influence of intellectual, emotional, and spiritual intelligence on performance, and the indirect influence of intellectual, emotional, and spiritual intelligence on performance through job satisfaction of the educational staffs of University of Jember (UNEJ). This research is an explanatory research with quantitative approach. The sample consists of 154 respondents, i.e., the educational staffs of the head office of UNEJ. This research uses Structural Equation Modeling (SEM) to analyze causal relationship among variables and test the proposed hypothesis. The results of the research show that intellectual intelligence has a positive and significant influence on job satisfaction and performance; emotional intelligence has a positive and significant influence on job satisfaction and performance; spiritual intelligence has a positive and significant influence on job satisfaction and performance; and job satisfaction has a positive and significant influence on performance. Keywords: Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence, Job Satisfaction, and Performance